2021
DOI: 10.1108/bpmj-02-2021-0111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of knowledge management processes on organizational performance: the mediating role of absorptive capacity

Abstract: PurposeExisting research on knowledge management processes (KMPs) and absorptive capacity (ACAP) is primarily conceptual and descriptive in nature, and empirical research confirming the real impact of KMPs when developing ACAP is lacking. Furthermore, the relationship between ACAP and organizational performance (OP) has not been adequately studied. Hence, the purpose of this paper is to introduce a comprehensive, delineated and integrated conceptual model which encompasses KMPs, ACAP and OP. Then, an empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 147 publications
(213 reference statements)
2
18
1
Order By: Relevance
“…Migdadi (2022) identified a strong correlation between knowledge governance and tacit knowledge sharing in projects, as supported by the findings from the present study. This study’s findings also point to the critical significance of knowledge governance in directing project-level knowledge management activities and complement the conclusion of Pemsel et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Migdadi (2022) identified a strong correlation between knowledge governance and tacit knowledge sharing in projects, as supported by the findings from the present study. This study’s findings also point to the critical significance of knowledge governance in directing project-level knowledge management activities and complement the conclusion of Pemsel et al.…”
Section: Discussionsupporting
confidence: 88%
“…The research reveals that tacit knowledge sharing does not substantially impact project performance but does help strengthen the site's absorptive capacity and results in better performance measurement, which is also an area where current studies suggested further studies (Biloslavo and Lombardi, 2021;Sharma and Phookan, 2022). Migdadi (2022) identified a strong correlation between knowledge governance and tacit knowledge sharing in projects, as supported by the findings from the present study. This study's findings also point to the critical significance of knowledge governance in directing project-level knowledge management activities and complement the conclusion of Pemsel et al (2016), which indicates that successful knowledge governance is a mandatory requirement for effective tacit knowledge sharing.…”
Section: Tacit Knowledge Sharingsupporting
confidence: 71%
“…Despite the uniqueness and unrepeatability of projects, the situations faced by managers and team members can be repeated. Therefore, knowledge sharing between projects is important [2,61]. Proper knowledge sharing in projects ensures a successful project output [62].…”
Section: Discussionmentioning
confidence: 99%
“…Shahzad et al (2020) found that knowledge management can improve corporate performance. A study found that the knowledge management process can boost enterprise worker productivity, leading to improved enterprise productivity (Migdadi, 2022). Similarly, an empirical analysis of data from 88 Italian SMEs showed that managing with knowledge can promote extensive data analytics capabilities, improving firm performance (Ferraris et al, 2019).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%